The multiwalled nanotubes based on titania and vanadia as polyfunctional compounds of platinum catalysts for carbon monoxide afterburning - А. V. Grigorieva; А. B. Тarasov; Т. А. Anufrieva; L. Е. Derlyukova; А. S. Vyacheslavov; E. A. Goodilin (Тонкие химические технологии, 2008)
We examined the possibility of application of nanotubes based on titanium dioxide and vanadium pentoxide as catalysts for carbon monoxide oxidation. The efficiency of TiO2 nanotubes in this process was confirmed